De l'ambiguïté des segments averbaux en français parlé - Tanguy, Noalig (My University, 2009)
Verbless segments can play many different roles. These roles range from working as a sentential constituent to being a predicate. Yet, their analysis in spoken French is not always straightforward. In this article, we shall study two cases when the syntactic interpretation of verbless segments in spoken French is ambiguous:
(i) verbless segments which can be given different statuses.
(ii) complements which can be postponed, verbless constituents which partake of the three following categories: integrated elements, detached elements and autonomous elements.
We shall assess the efficiency of the various means used to disambiguate the interpretation of these segments, i.e. the use of the linguistic context, of the prosodic and semantic levels, of word order, etc.